Timing of Delivery in Intrahepatic Cholestasis of Pregnancy With Total Bile Acids ≥100 µmol/L: A Decision Analysis [38N]. (May 2020) - Frank, Zoe C.; Nienow-Birch, Mary N.; Lo, Jamie; Shaffer, Brian L.; Caughey, Aaron B.
Abstract : INTRODUCTION: Our study models the trade-off between preterm neonatal morbidity and stillbirth for women with intrahepatic cholestasis of pregnancy (ICP) with total bile acids ≥100 µmol/L in order to determine the optimal gestational age for delivery. METHODS: A decision analytic model was created to compare the outcomes of delivery at 33 through 40 weeks gestation in women with total bile acids (TBA) ≥100 µmol/L. Baseline risks of stillbirth and spontaneous delivery were derived from the literature and adjusted for peak TBA. It was assumed that betamethasone was given within 48 hours of all planned preterm deliveries and before a percentage of spontaneous ones. We assumed a population of 10, 000 women with ICP and calculated total quality-adjusted life years (QALYs) for each strategy, taking into account both maternal and neonatal perspectives. Univariate sensitivity analysis was performed for all variables to test the robustness of the model. RESULTS: In women with peak TBA ≥100 µmol/L, delivery at 34 weeks maximized QALYs. Compared to delivery at 36 weeks, it resulted in 1302.4 more QALYs, 98.2 fewer stillbirths, and 21 more cases of cerebral palsy in our theoretical cohort of 10, 000 women. Sensitivity analysis demonstrated that when the relative risk of stillbirth given TBA ≥100 µmol/L fell from a baseline of 30.5 to below 26.2, delivery at 35 weeks became optimal. Monte Carlo analysis demonstrated that when variation was incorporated into the model, delivery at 34 weeks was the dominant strategy 45% of the time. CONCLUSION: In women with ICP with TBA ≥100 µmol/L, delivery at 34 weeks maximizes QALYs.